The Oxford handbook of evidentiality (Oxford handbooks in linguistics., 2018)
This volume offers a systematic crosslinguistic account of evidentiality, the linguistic encoding of the source of information on which a statement is based. It explores a range of topics relating to evidentiality and provides case studies from a variety of language families as diverse as Algonquian, Korean, and Uralic.